A DFT Study the Electronic, Optical and Thermal Properties of XTe (X= Pb, Cd, Nb) for optoelectronic device Applications - Zorah, Mohammed (Technium BioChemMed, 2024)
A First-principles based study to investigate the different properties of telluride (Te) based materials XTe (X= Pb, Cd, Nb) such as structural, electronic, optical, and thermal properties. The bandgap of XTe (X= Pb, Cd, Nb) was originate significantly decrement from 1.50 eV to 0.00 eV. Under the First-principles exploration Pb, Cd, and Nb are appropriate periodic elements for bandgap decrement in XTe materials. The bandgap nature was obtaining direct furthermore bandgap show that materials are proficient semiconductors. Niobium (Nb) is more advantageous than Pb and Cd. By substituting of X= Pb, Cd, Nb at the corner sites in XTe (X= Pb, Cd, Nb) additional gamma sites were participated in the electronic energy band gap (Eg). It is also examined that optical peaks shifted toward larger energy due to decrement in the band gap. Thermal impact on macroscopic properties of XTe (X= Pb, Cd, Nb) compounds are predicted using the quasi-harmonic Debye model. The variations of the enthalpy (U-U), entropy (S-S), heat capacity, Debye temperature, and free energy with temperature function are obtained successfully. Moreover, small band-gap semiconducting Telluride (Te) based materials reveal low thermal conductivities at a prominent temperature which is curious for simple cubic structured materials. These compounds for electrical, optical, and thermal properties have made them practical novel materials for optoelectronic device applications.